- #1

nietzsche

- 186

- 0

This is a homework question, but it's for symbolic logic. Figured that it didn't really make sense to post it with the math and science questions, although I'm sure people on there would know how to solve it.

I'm having trouble constructing a derivation for the following:

For all x, (Bx -> Ex).

There exists some y such that (Ay -> ~Ey).

Therefore, there exists some z such that (Az ^ ~Bz).

(Don't know how to do the symbols...)

I changed the second premise into (~Aa v ~Ea), but I don't know what to do with that. I can see that if I have Aa to begin with, then Aa -> ~Ea -> ~Bx.

But what if I have ~Ea to begin with? That's what I'm having trouble with.

Or maybe I'm looking at it the wrong way?

Hope someone on here can help me. Thanks in advance.